Market-Oriented Institutional Change and R&D Investments: Do Business Groups Enhance Advantage? - CHOI, Young Rok (Institutional Knowledge at Singapore Management University, 2014)
Emerging market firms (EMFs) are increasingly relying on innovation to find their competitive advantage, but our understanding of how institutional change affects firm innovation has been limited. We analyzed Korean manufacturing firms from 1994 to 2006 to test the proposition that market-oriented institutional change in an emerging economy alleviates firms’ financing constraints and monitoring problems and improves the effectiveness of their innovation activities. Institutional evolution in the economy was found to affect Korean business groups and independent firms differently. Institutional change reduced the financing constraints on independent firms more than for business group affiliates in R&D investment. Independent firms, however, appeared less capable than group affiliates of translating the benefits of improved institutional environments into efficient R&D investment. This asymmetry may lead to a wider gap in the efficiency of R&D investment between business group affiliates and independent firms.